Effects of processing on the nutrient composition of rubber seed meal - M.D. Udo; U. Ekpo; F.O. Ahamefule (Journal of the Saudi Society of Agricultural Sciences)
The nutritive value of raw and processed rubber seed meal (Hevea brasiliensis) was investigated by considering the following parameters – proximate composition, gross energy, mineral composition and anti-nutritional factors. The raw and processed seeds were dried, milled and chemically analysed. Crude protein contents of the raw and processed rubber seeds ranged between 21.08% and 24.60%, while the crude fibre values ranged between 4.47% and 5.88%. The gross energy content for the raw had significantly (P < 0.05) higher values than the processed. Mineral content (macro and micro) of seeds boiled was significantly (P < 0.05) higher than other processing methods. Also, seeds boiled had significantly (P < 0.05) lower values in all anti-nutritional factors, with hydrogen cyanide and trypsin inhibitor completely destroyed by both boiling and toasting. With high value of crude protein (24.60%), appreciable energy content (2.32 MJ/kg), highest value of macro and micro minerals and significantly lower values in all the anti-nutritional factors for the seeds boiled, boiling is therefore recommended for usage in livestock and poultry ration. Keywords: Nutritive value, Rubber seed meal, Processing methods, Livestock, Poultry